Aprender Mais em Fortaleza: uma avaliação da política de Educação integral em uma escola municipal - Silva, Samuel Aquino Vieira da (2024)
This dissertation evaluates the Aprender Mais Program, a comprehensive education initiative implemented in Fortaleza, Ceará. The study focuses on the Aprender Mais Escola modality, one of the six modalities of the program, and contextualizes it within the trajectory of policies to extend the school day in Brazil. The research is situated at the intersection of public education policies and pedagogical practices, seeking to understand how Aprender Mais materializes in the daily school routine. The general objective is to evaluate how the Aprender Mais Program is implemented in a municipal public school in Fortaleza, from 2019 to 2024. The specific objectives are: to recognize the concept of comprehensive education in the Aprender Mais Program; to understand how school management uses the Aprender Mais Program to contribute to student learning; to analyze the perceptions of different actors about the program in the daily school routine. The research adopts a qualitative approach, using the case study method and in depth evaluation. The data collection instruments used were: document analysis, interviews with different actors in the school community (managers, teachers, mediators, parents and technicians from the Municipal Department of Education) and direct observation at the school. The results of the research indicate that the Aprender Mais Program, although representing progress in the search for a fairer and more comprehensive education, is still in a construction process and faces challenges that require attention from public administrators and the school community. Among the challenges, the need to improve the training of monitors, the infrastructure of schools and communication with families stands out. It is concluded that the Aprender Mais Program, in the Aprender Mais Escola modality, represents a search for a more equitable and comprehensive education, however, it is still in a dialectical process of construction and reconstruction, reflecting the broader challenges of comprehensive education in contemporary Brazil.